ON THE PRESTIGE OF THE UNIVERSITY TEACHER PROFESSION, POSTGRADUATE ACADEMIC DEGREES AND TITLES - Vasily S. Senashenko (Высшее образование в России)
The article discusses the problem of the prestige loss of the university teacher profession, postgraduate academic degrees and titles. The main reasons for lowering the prestige of the key components of educational environment quality have been identified. A slow increase in social status of pedagogical and scientific workers of educational and scientific organizations has been marked out. The increasing complexity and diversity of university teachers' activities are highlighted. The author comes to a conclusion that special road map is needed to raise the university teachers' prestige and social status. The academic community should initiate developing the complex measures aimed at creating the new legal and normative provision of a university teacher's activities in the new social and economic conditions.